Outcome predictors of meningoencephelitis due to Orienta tsutsugamushi in children: a retrospective study in tertiary care hospital in the terai region of West Bengal - Bagchi, Nilay Ranjan (International Journal of Contemporary Pediatrics, 2022)
Background: Childhood infection by Orienta tsutsugamushi is endemic in India and central nervous system invasion by this organism is exceedingly high which is difficult to diagnose. Meningoencephelitis is a life-threatening manifestation of febrile illness caused by orienta tsutsugamushi that can cause significant morbidity and case fatality. Early diagnosis of mortality indicators and judicious intensive treatment accordingly can reduce mortality. Methods: A retrospective study was conducted with 22 patients of meningoencephelitis due to Orienta tsutsugamushi to find out the mortality predictors in the department of pediatrics of North Bengal medical college, Darjeeling, West Bengal, India Results: It was seen that Pneumonitis, raised SGPT, Oedema and raised creatinine were found to be poor prognostic indicators of orienta tsutsugamushi meningoencephelitis. Conclusions: Identification of those predictors and early initiation of intensive management accordingly will be salutary to reduce mortality in orienta tsutsugamushi meningoencephelitis.